2014
DOI: 10.2131/jts.39.687
|View full text |Cite
|
Sign up to set email alerts
|

<i>S</i>-Mercuration of cellular proteins by methylmercury and its toxicological implications

Abstract: -The accumulation of methylmercury (MeHg) through the daily consumption of large predatory fish poses potential health risks. MeHg has been found to cause Minamata disease, but the full nature of MeHg toxicity remains unclear. Because of its chemical properties, MeHg covalently binds to cellular proteins through their reactive thiols, referred to as S-mercuration, resulting in the formation of protein adducts. In this review, we summarize how the S-mercuration of cellular proteins could be involved in the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 126 publications
(123 reference statements)
4
27
0
Order By: Relevance
“…Mitochondrial thiol status and antioxidant levels were found to be significantly declined due to MeHg exposure which could be due to the covalent binding of MeHg to reactive thiols of cellular proteins. MeHg exposure induced reduction in antioxidant levels has been reported in earlier studies (Farina et al, 2011; Kanda et al, 2014). Out of the four doses studied, 30 mg/kg b.w.…”
Section: Discussionsupporting
confidence: 73%
“…Mitochondrial thiol status and antioxidant levels were found to be significantly declined due to MeHg exposure which could be due to the covalent binding of MeHg to reactive thiols of cellular proteins. MeHg exposure induced reduction in antioxidant levels has been reported in earlier studies (Farina et al, 2011; Kanda et al, 2014). Out of the four doses studied, 30 mg/kg b.w.…”
Section: Discussionsupporting
confidence: 73%
“…Methyl mercury (MeHg) is one of the most toxic species of Hg which is assimilated into the water and food, and biomagnifies upwards in food chains 4 . MeHg can induce changes in mitochondria dyshomeostasis, increase the generation of reactive oxygen species, disturb oxidative phosphorylation and electron transport 5, 6 which lead to lipid peroxidation and cell death 68 . It has long been observed that selenium (Se) protects organism from the toxicity of MeHg 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Methylmercury is an environmental pollutant known as the cause of Minamata disease, and severe central nervous system damage123. In sea- and fresh water, methylmercury bioaccumulates through the food chain to relatively high concentrations in the muscle of fish.…”
mentioning
confidence: 99%